Chromatographic determination of plant saponins - Oleszek, W.A.
The methods used for saponin determination in plant materials are presented. It is emphasised that the biological and spectrophotomeric methods still being used for saponin determination provide, to some extent, valuable results on saponin concentrations in plant material. However, since they are sensitive to the structural variation of individual saponins they should be standardized with saponin mixtures isolated from the plant species in which the concentration is measured. However, one plant species may contain some saponins which can be determined with a biological test and others which cannot. That is why biological and colorimetric determinations do not provide accurate data and have to be recognized as approximate. Thin-layer chromatography on normal and reversed-phases (TLC, HPTLC, 2D-TLC)provides excellent qualitative information and in combination with on-line coupling of a computer with dual-wavelength flying-spot scanner and two-dimensional analytical software can be used for routine determination of saponins in plant material. The densitometry of saponins has been very sensitive, however, to plate quality, spraying technique and the heating time and therefore appropriate saponin standards have to be run in parallel with the sample. Gas-liquid chromatography has limited application for determination since saponins are quite big molecules and are not volatile compounds. Thus, there are only few applications of GC for determination of intact saponins. The method has been used for determination of TMS, acetyl or methyl derivatives of an aglycones released during saponin hydrolysis. However, structurally different saponins show different rates of hydrolysis and precise optimisation of hydrolysis conditions is essential. Besides, during hydrolysis a number of artefacts can be formed which can influence the final results. High performance liquid chromatography on reversed-phase columns remains the best technique for saponin determination and is the most-widely used method for this group of compounds. However, the lack of chromophores allowing detection in UV, limits the choice of gradient and detection method. The pre-column derivatisation with benzoyl chloride, coumarin or 4-bromophenacyl bromide has been used successfully in some cases allowing UV detection of separation. Standardisation and identification of the peaks in HPLC chromatograms has been based on comparison of the retention times with those observed for authentic standards. But new hyphenated techniques, combining HPLC with mass spectrometry and nuclear magnetic resonance are developing rapidly and allow on-line identification of separated saponins. Capillary electrophoresis has been applied for saponin determination only in a limited number of cases and this method is still being developed.
Keywords: SAPONINS; TRITERPENE GLYCOSIDES; STEROIDAL GLYCOSIDES